Management of Green Open Space in the Karanganyar Regency Government Based on the Principles of Good Environmental Governance - Andhika Satrio Kusumo; Rosita Candrakirana (MultiTech Publisher, 2024)
The high level of industrial development in Indonesia is parallel to population growth which has an impact on changes in land use. Green Open Space or RTH is the smallest part of an area in a city or district which is used not only as an aesthetic area but also as a green area as a place for community activities with a health connotation. Green open areas in Karanganyar Regency have not yet reached the applicable standards by Karanganayar Regency Regional Regulation No. 12 of 2022 concerning the Management of Green Open Spaces. The research method uses qualitative descriptive and data collection techniques by interviewing various data sources, conducting direct observations in the field, library research, documentation. Government websites and Instagram, transparency, and accountability, access to information through local government websites, and reporting in the annual LKPJ, decentralization is not yet strong enough but decision-makers are still the authorities and institutions and agencies, do not have their own RTH institutions, but each section carries out duties according to its main duties, access to law enforcement, complaints are submitted on the online public application and complaint service website, and the open spaces of Karanganyar Regency can be accessed by the public. The overall analysis is quite good, but several aspects are less than optimal, namely decentralization. So there needs to be innovation from the Karanganyar Regency government.